A retrospective review of western lowland gorilla (gorilla, gorilla, gorilla) mortality in European zoological collections between 2004 and 2014 - Strong, Victoria; Baiker, Kerstin; Brennan, Marnie L.; Redrobe, Sharon; Rietkerk, Frank; Cobb, Malcolm; White, Kate (American Association of Zoo Veterinarians, 2017)
An understanding of the main causes of mortality among captive gorillas is imperative to promoting their optimal care, health, and welfare. A retrospective observational review of mortality among the European zoo–housed western lowland gorilla (Gorilla gorilla gorilla) population from 2004 to 2014 was carried out. This is the first published study of mortality in this population. Relevant postmortem data were requested from each collection reporting a death during the study period. Age at death enabled grouping into discrete age categories. Deaths were classified according to cause. The main causes of death overall and for each age category and sex were identified. In total, 151 gorillas from 50 European collections died during the study period. Postmortem data were available for 119 (79%) of the deaths, of which 102 (86%) were classified by cause. Diseases of the digestive system were responsible for most (23%) deaths overall. Also of significance (each accounting for 15% overall mortality) were deaths due to external causes (especially trauma) among young gorillas and cardiovascular disease among adult and aged animals. Being a male gorilla was associated with an 8.77- and 5.40-fold increase in risk of death due to cardiovascular and respiratory disease, respectively. Death due to external causes was 4.45 times more likely among females than males. There was no statistically significant difference in life expectancy between male and female gorillas. The authors conclude that further work is needed to understand risk factors involved in the main causes of death and suggest a need for standardization with regard the approach to postmortem examination and data collection, sample collection, and storage across European zoos.